European Emission Trading Scheme at a Turning Point – From the Pilot Phase to Post-2012 - Aura Carmen Slate (Romanian Journal of European Affairs)
Climate change action has become a top priority for the European governments and for the European Union. Since the polluters are part of the energy-intensive industries, the mechanisms designed to reduce greenhouse gas emissions should focus on the economic sector as a primary source of concern. Therefore, environmental issues interrelate with the economic ones and one viable expression of this relation is the EU ETS, a cap-and-trade mechanism. The ETS started with a pilot phase in year 2005 and will continue with a third phase after 2012, period which coincides with the end of Kyoto’s commitment. Although statistical data prove that the EU ETS is becoming more efficient with each phase, in the absence of global involvement the efforts invested in the scheme will be made in vain.